2000
DOI: 10.1002/chin.200048218
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phyllanthusols A and B, Cytotoxic Norbisabolane Glycosides from Phyllanthus acidus Skeels.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
3
3
0
1
Order By: Relevance
“…P .piscatorum and P. flaccidus which were positive to 9 and 8 phytochemical tests respectively. These results are in parallel to the earlier studies conducted on terpens , alkaloids , lignans , flavonoids and tannins in Phyllathus species (Vongvanich et al, 2000;Houghton, 1999;Lin et al, 1995). The results of the phytochemical tests on B. ferruginea confirms the studies on the same by Kabir, where he reported the presence of alkaloids, tannins, saponins and flavonoids (Kabir et al, ).…”
Section: Resultssupporting
confidence: 88%
“…P .piscatorum and P. flaccidus which were positive to 9 and 8 phytochemical tests respectively. These results are in parallel to the earlier studies conducted on terpens , alkaloids , lignans , flavonoids and tannins in Phyllathus species (Vongvanich et al, 2000;Houghton, 1999;Lin et al, 1995). The results of the phytochemical tests on B. ferruginea confirms the studies on the same by Kabir, where he reported the presence of alkaloids, tannins, saponins and flavonoids (Kabir et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Lignans, tannins and phenols were detected in all the 3 tested plants. These results are in parallel to the earlier studies conducted on terpenes, alkaloids, lignans, flavonoids and tannins in Phyllanthus species [18][19][20][21] . The difference in the findings might be due to the nature of the solvent used for extraction, which determines the presence or absence of a metabolite in the extract.…”
Section: Phenetic Relationshipsupporting
confidence: 90%
“…(Euphorbiaceae). Isolation of phyllanthocin from Phyllanthus brasiliensis Muell (Kupchan et al, 1977), phyllaemblicins A-F and G1-G8 from Phyllanthus emblica Linn (Lv et al, 2014a;Zhang et al, 2000aZhang et al, ,b, 2001, and phyllanthacidoids A-U from Phyllanthus acidus Skeels (Lv et al, 2014b;Vongvanich et al, 2000) have been previously reported. These compounds showed potent antileukemic (Kupchan et al, 1977), cytotoxic (Vongvanich et al, 2000) and anti-viral (Liu et al, 2009;Lv et al, 2014a,b) activities, which attracted considerable attention by pharmacologists and organic chemists (Moore and Powis, 1986;Smith et al, 1991).…”
Section: Introductionmentioning
confidence: 90%